Emerging cyber capabilities in the Asia Pacific : potential military impact - Caitriona H. Heinl (2014)
The Asia Pacific comprises diverse countries with conflicting ideologies and different states of development. Given the variety of challenges and tensions over territorial disputes and geopolitical uncertainties across the region, a careful analysis of cyber capabilities and their possible impact would be valuable.